The Role of Islamic Religious Education in Promoting Religious Moderation and Social Harmony in Multicultural Societies - AGUS TOHAWI (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
This study investigates the role of Islamic Religious Education in fostering religious moderation and social harmony within multicultural societies. Using a descriptive qualitative method, data were collected through interviews, focus group discussions, and curriculum analysis. The findings demonstrate that IRE plays a strategic role in promoting inclusive values, tolerance, and respect for diversity when moderation principles are explicitly integrated into learning objectives and teaching practices. Teachers’ interpretative approaches and contextualized learning materials significantly influence students’ attitudes toward pluralism. The study underscores the importance of reorienting Islamic education toward moderation as a means of strengthening social cohesion. These findings offer practical insights for policymakers and educators in multicultural educational settings.